GENETIC VARIATION AND POPULATION STRUCTURE IN THE HUMPBACK GROUPER, Cromileptes altivelis, TROUGHOUT ITS RANGE IN INDONESIAN WATERS - Ketut Sugama; Tridjoko Tridjoko; Haryanti Haryanti; Sari Budi M; Fuad Cholik (Indonesian Fisheries Research Journal, 1999)
Starch gel electrophoresis was used to assess the level and distribution ofgenetic variation in humpback grouper, Cromileptes altiuelis sampled from 4 different areas of coral reefs in Raas and Kangean located in Madura as well as Sangeang and Bungin located in Sumbawa regions, between December 1997 and March 1998.